Nanoscale Organisation of Ryanodine Receptors and Junctophilin-2 in the Failing Human Heart - Hou, Yufeng; Bai, Jizhong; Shen, Xin; de Langen, Oscar; Li, Amy; Lal, Sean; dos Remedios, Cristobal G.; Baddeley, David; Ruygrok, Peter N.; Soeller, Christian; Crossman, David J. (Frontiers in Physiology, 2021)
The disrupted organisation of the ryanodine receptors (RyR) and junctophilin (JPH) are thought to underpin transverse(t)-tubule remodelling in the failing heart. Here we assessed the nanoscale organisation of these two key proteins in the failing human heart. Recently an advanced feature of t-tubule remodelling large flatten t-tubules called t-sheets were identified that can be several microns wide. Previously, in the failing heart, we have identified that dilated t-tubules up to ~1 µm wide had increased amounts of collagen and hypothesized that t-sheets would also be associated with collagen deposits. Direct stochastic optical reconstruction microscopy (dSTORM), confocal microscopy, and western blotting were used to evaluate the cellular distribution of excitation-contraction structures in the cardiac myocytes from patients with idiopathic dilated cardiomyopathy (IDCM) in comparison to myocytes from the non-failing human heart. dSTORM imaging of RyR and JPH found no difference in colocalisation between IDCM and non-failing myocytes but there was higher colocalisation at t-tubule and sarcolemma compared to corbular regions. Western blots revealed no change in JPH expression but did identify a ~50% downregulation of RyR (p=0.02). dSTORM imaging revealed a trend for smaller t-tubular RyR clusters (~24%) and reduced t-tubular RyR cluster density (~35%) that resulted in 50% reduction of t-tubular RyR tetramers in IDCM myocytes (P=0.01). Confocal microscopy identified t-sheets in all IDCM hearts examined and that these were associated with the reticular collagen fibres within their lumen. However, RyR clusters size and density was similar in myocyte regions associated with t-sheets and t-tubules. T-tubule remodelling is associated with reduced RyR expression that may contribute to reduced excitation-contraction coupling in the failing human heart.